Pitkern-Norf'k The Language of Pitcairn Island and Norfolk Island - Mühlhäusler, Peter (Dialects of English [DOE] ;, 2020)
This book tells the story of the language of the Bounty mutineers and their Polynesian consorts that developed on remote Pitcairn Island in the late 18th century. Most of their descendants subsequently relocated to Norfolk Island. It is an in-depth study of the complex linguistic, ecological and sociohistorical forces that have been involved in the formation and subsequent development of this unique endangered language on both islands.